Sheep fatigue during transport: Lost in translation? - Katia Colitti; Malcolm Mitchell; Fritha Langford (Animal Welfare, 2024)
Although sheep are commonly transported long distances, and sheep welfare during transport is a topic of research and policy discussion, the subject of their fatigue during transport has been under-researched. The current qualitative study, focused on the EU and UK, aimed to critically analyse stakeholder views on issues relating to sheep fatigue, including behavioural indications of fatigue, the interplay between fatigue and other factors, and the practicalities of identifying fatigue in commercial transport conditions. Insight into stakeholder perceptions of these issues could contribute to the body of knowledge regarding sheep fatigue during transport, potentially playing a part in future efforts to improve fatigue understanding and detection. Eighteen experts from different stakeholder groups were interviewed. Reflexive thematic analysis of interview data yielded four themes and three sub-themes. The first theme, “Let’s anthropomorphise it a little bit”, underscores the pervasiveness of anthropomorphism and suggests using it in a conscious and deliberate way to drive stakeholder engagement and policy change. The second theme, “We think that they’re like we are and they’re not”, cautions against wholesale transfer of human experiences to animals. The third theme, ‘See the whole animal’, advocates using Qualitative Behaviour Analysis (QBA), proven reliable in other contexts, to deepen and enrich our current understanding of fatigue. The fourth theme, ‘Fatigue “never comes up”’, highlights the fact that fatigue is rarely if ever discussed in the context of sheep transport. These themes suggest several avenues for future research, including developing QBA-based assessments for fatigue to improve welfare during transport.